Abundance and distribution of the endangered loggerhead turtle in Spanish Mediterranean waters and the conservation implications - Gómez de Segura, A. (2006)
During 2 years (2001–2003), we performed seasonal aerial surveys in the central Spanish Mediterranean following the transect line methodology in order to determine the abundance and distribution patterns of loggerhead turtles Caretta caretta. We surveyed a total of 16 700 km, accounting for 770 turtle sightings. Loggerhead turtles were present with high abundance all year round. No seasonal differences in abundance were found, except in spring 2001, where the density of turtles was higher than in the other seasons. Our results show that the Western Mediterranean is not a ‘summer’ feeding area as proposed previously, as a high number of turtles are present throughout the year. The average surface density of turtles in the whole study area was 0.21 turtles km 2 [95% conﬁdence interval (CI): 0.17–0.25], and the mean abundance was 6653 turtles (95% CI: 5514–8027). The data relate to the number of turtles on the surface only, as diving turtles escape observation. Correcting our estimations of diving behaviour data in the area, the absolute abundance was 18 954 turtles (95% CI: 6679–53 786). Bearing in mind that around 25 000 loggerheads are caught per year in the Spanish Mediterranean, our results indicate that accidental captures seem to be a signiﬁcant threat for this species, and conservation measures have to be implemented to avoid a non- sustainable situation.